MODEL LEARNING MANAGEMENT SYSTEM (LMS) PADA PEMBELAJARAN PAI DI SMP ISLAM AL-AZHAR 2 JAKARTA - Oktaria, Auline; Khadijah, Siti; Miranto, Sujiyo (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Problems in PAI learning are often encountered, namely the superiority of PAI learning is still low, how to educate parents, environment, climate, strict teachers. The purpose of this study is to describe the model, preparation, implementation, evaluation, follow-up and analysis of the learning constraints of the LMS model in PAI learning. This type of research is qualitative with a case study approach that is critical-analyst with data collection techniques of observation, interviews and documentation. The results of this study are: (1) The use of technology is very important to support modern learning activities; (2) In planning learning with LMS, the teacher makes syllabus and lesson plans, determines, designs the methods and media used when learning with LMS; (3) The implementation of PAI learning begins with greetings, opening by the teacher, checking student attendance, providing stimulus, providing teaching materials by presenting teaching materials using LMS; (4) In the evaluation there are affective, cognitive and psychomotor assessments, with supporting applications such as quizizz, interactive videos, google forms, for UTS and UAS using the LMS application with integrated questions from Al-Azhar Center; (5) Follow-up to PAI learning requires training and socialization of LMS; (6) Factors inhibiting PAI learning with LMS: LMS system disturbances, internet network disturbances, display features and notifications on the Al-Azhar LMS are out of sync, the smartphone LMS application needs to be upgraded